Production of Copper Powder from Ores by Elecrodeposition Process (Journal of University of Babylon for Engineering Sciences, 2019)
This paper studies the preparation of Copper powder from copper sulphate aqueous solution (CuSO4.5H2O), sulfuric acid (H2SO4) and copper chloride (CuCl2.2H2O) by using the process of electrodeposition. Process of Powder deposition has been investigated for copper powder; it is a fine layer on cathode electrode by using the value of different from time of deposition (15, 30, 45, and 60) min. it is noticed the weight of the powder rises with the rise of time of depostion.Diffractions of X-ray (XRD) revealed high crystallinity and pure copper powder not contain impurity or oxides. Optical microscopes have revealed the particles of copper have dendritic shapes. The size of Particles analyzer measured the size of a particle which is about (4.645) μm.